The Synergy of Parents and School Involvement in Children Consumer Education since Early Childhood - Triwijayati, Anna (Proceedings Series on Physical & Formal Sciences, 2022)
Children consumer education since their early childhood is important to be done by involving parents and school. Children learn to become consumers; and consumer education on children is obtained from their parents and school. This paper is based on a continuous research on children consumers which is aimed at building the synergy of parents and school involvement in children consumer education since their early childhood. The research was conducted in Malang City, involving elementary schools in a Forum Group Discussion. This research uses qualitative paradigm and is in the method of phenomenology research. The research findings yield a school program that involves parents, namely canteen monitoring; the control of canteen menu and snacks which is conducted by schools; the education of healthy snacks for parents; involving students’ parents who would like to sell snacks in the canteen; make the children have their breakfast; include the materials of healthy snacks and food additives in the materials of Physical Education and Health curriculum; educating children so that they choose healthier food; empowering children more with the emphasis and learning about the effects of food; giving information about the ingredients and contents of food as well as the expiry date and interesting children education materials.